LABOR INDUCTION: PREGNANCY AND CHILDBIRTH OUTCOMES, ITS IMPACT ON NEWBORNS STATUS - Оксана Николаевна Новикова; Ольга Александровна Соломатина (The Publishing House Medicine and Enlightenment, 2018)
Aim: To study specific characteristics of the course of pregnancy and labor, newborn status in labor induction. Materials and Methods. 216 maternal/newborn medical records in the maternity hospital N 1, State Autonomous Healthcare Institution «Podgorbunsky M.A. Regional Clinical Hospital of Emergency Health Service» in 2016, were retrospectively reviewed. The study group (Group 1, n = 108) included women and their newborns after induction of labor, and the control group (Group 2, n = 108) - women and their newborns after spontaneous labor. Inclusion criteria were as follows: 37-41 weeks of gestation, induction of labor, singleton pregnancy. Exclusion criteria were as follows: premature birth, the presence of maternal/fetal diseases or conditions, requiring C-section. Results. Indications for labor induction included an exacerbation of somatic pathology in 42 patients (32,1 %), preeclampsia, resistant to conservative management - in 33 (27,2 %); premature rupture of membranes (PROM) without any signs of spontaneous labor in full term pregnancy - in 16 (11,3 %), postterm pregnancy - in 27 patients (22,9 %). The Bishop score of less than 6 points indicates an unripe cervix, 6-8 points - a poor cervical ripening, over 8 points - a ripe cervix. Thus, 10 patients (9,6 %) had unripe cervices, 27 (26,0 %) - a poor cervical ripening and 69 (65,4 %) - ripe cervices. Аt 10 (9,2 %) during pregnancy by results of ultrasonography the low placentation, at 12 (11,1 %) the broken amount of amniotic waters was revealed; at 29 fruits (26,8 %) violations of KTG as borderline cases of action of the heart are revealed. The most common labor complications were trauma in labor: 66 patients (66,7 %) in the study group vs. 18 patients (60 %) in the control group, p < 0,05), abnormal labor (37 patients (34,2 % ) vs. 4 patients (13,8 %), p < 0,05, respectively) including uterine inertia (21 patients (18,7 %) vs. 2 patients (3,1 %), p < 0,05, respectively) and incoordinate uterine activity (17 patients (15,5 %) vs. 1 patient (2,6 %), p < 0,05, respectively. Conclusions. Labor induction is associated with increased blood loss, higher rates of abnormal labor, birth canal traumaand prolonged postnatal hospital stay in newborns.